New Forms of Ownership - Portis, Bernard (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "New Forms of Ownership," edited by Glenville Jenkins and Michael Poole
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Corporations; Labor Unions; Reorganization; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z